Situs Megalitik Tutari sebagai Sumber Inspirasi Penciptaan Koreografi Site-Specific “Tutari MegArt Lithic” - Sri Rustiyanti (Dance and Theatre Review, 2021)
The Tutari Megalithic Site is a large stone age civilization site located in Doyo Lama Village, Waibu District, Jayapura Regency, Papua. Visually, on this site, there are stones with various motifs of prehistoric paintings on them. However, if it is studied in-depth, primarily through the perspective of choreography, this site has a broad potential to be a source of inspiration for creating works of art. Collaborating with previous research from the Papua Archeology Center, the creation of this Tutari MegArt Lithic artwork is focused on specific parts of the Tutari Megalithic site that can be used as inspiration for creating artworks. The method used in this writing is descriptive analysis. The purpose of this paper is to provide an overview of how choreography can collaborate across disciplines in the creation of works of art staged at the Tutari archaeological site. This paper describes the sources of inspiration for creating site-specific choreographic works of art entitled Tutari MegArt Lithic, including visual inspiration, artistic inspiration and idea inspiration.Keywords: Tutari Megalithic Site; site-specific choreography; source of inspiration; painting motive